Clouds and hazes in Saturn's troposphere and stratosphere - Merlet, CTC (2013)
The cloud and haze properties in the troposphere and stratosphere of Saturn are investigated in this thesis by analysing Cassini/VIMS spectra at 0.8-3.5 μm and 4.5-5.1 μm. The aerosol properties are derived from VIMS data by using the retrieval tool NEMESIS developed at the University of Oxford. Near-infared VIMS data between 4.5 and 5.1 μm are mainly sensitive to deeper tropospheric levels down to approximately 5 bar. At such pressure levels, thermochemical models predict the formation of condensed clouds made of ammonia and ammonium hydrosulphide ices, although none of these species has been spectrally detected so far. In addition, phosphine and ammonia are responsible for most of the gaseous absorption at these wavelengths. Therefore, the cloud properties and gas distributions can be retrieved from VIMS near-infared spectra. In this thesis, the analysis of limb-darkening data at 4.5-5.1 μm is performed in order to constrain the aerosol properties in Saturn’s atmosphere. The best-fitting model consists of a scattering cloud between 2 and 3 bar, and a scattering haze layer which can be placed anywhere between 10 and 500 mbar. The composition is still poorly constrained for both the deep cloud and haze layer. The haze physical and optical properties can however be independently retrieved from VIMS near-infrared spectra at shorter wavelengths in the 0.8-3.5 μm spectral range. Saturn’s hazes in the troposphere and stratosphere reflect the sunlight at 0.8-3.5 μm. The properties and vertical structure of tropospheric and stratospheric hazes are then investigated from VIMS reflection spectra in the near-infared. The latitudinal variation of haze properties is compared to a thermal feature known as "the temperature knee", corresponding to a local increase of temperature right below the tropopause. The north-south temperature variations in the troposphere are obtained from the analysis of thermal infrared data measured with the Composite InfraRed Spectromete (CIRS) instrument on board Cassini. Finally, VIMS near-infrared data at 0.8-3.5 and 4.5-5.1 μm are combined in order to obtain a cloud and haze model coherent with both wavelength ranges.